2004
DOI: 10.1086/382240
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Polarimetry and Photometry of Recent Comets

Abstract: We present near-infrared (2.2 m) imaging polarimetry and near-infrared photometry for recent comets. The 2.2 m polarization as a function of phase angle is 1%-2% higher than typical comet visual narrowband red polarization. This implies a general, but weak, trend to higher polarization at wavelengths longer than 0.7 m. As found with visual narrowband red polarimetry, comets appear to divide into a high-and a low-polarization class at 2.2 m as well. The high-polarization class is characterized by moderate to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 35 publications
4
31
0
Order By: Relevance
“…However, at larger phase angles, where phase curves are possibly less constrained, the polarization values seem to be below the high-P max phase curve. In near infrared domain (H and I bands), at about 36°, the data points by Jones et al, (2008) are above the high-P max phase curve in red wavelength as usually observed for comets (Hadamcik and Levasseur-Regourd, 2003b;Kelley et al, 2004) and called 'positive polarimetric spectral gradient', but at larger phase angles than 40° (80°-90°, Bonev et al, 2008;Jones et al, 2008;Kiselev et al, 2008), they are below the synthetic red phase curve (negative polarimetric spectral gradient). The more neutral or slightly negative spectral gradient in the near infrared domains as observed for the two SW3 fragments at large phase angles, was previously observed for different comets e.g.…”
Section: Comparison Between Polarimetric Observations Of Sw3 and Thosmentioning
confidence: 53%
“…However, at larger phase angles, where phase curves are possibly less constrained, the polarization values seem to be below the high-P max phase curve. In near infrared domain (H and I bands), at about 36°, the data points by Jones et al, (2008) are above the high-P max phase curve in red wavelength as usually observed for comets (Hadamcik and Levasseur-Regourd, 2003b;Kelley et al, 2004) and called 'positive polarimetric spectral gradient', but at larger phase angles than 40° (80°-90°, Bonev et al, 2008;Jones et al, 2008;Kiselev et al, 2008), they are below the synthetic red phase curve (negative polarimetric spectral gradient). The more neutral or slightly negative spectral gradient in the near infrared domains as observed for the two SW3 fragments at large phase angles, was previously observed for different comets e.g.…”
Section: Comparison Between Polarimetric Observations Of Sw3 and Thosmentioning
confidence: 53%
“…It is therefore possible that the trichotomy in polarization is an artefact and that the cometary dust in the coma is characterized in all cases by high values of P max . Kelley et al (2004) have shown that the polarization of comets in the near IR (up to the K band) shows a weak trend to higher values at higher wavelengths, resembling the color effect observed at visible wavelengths. Comets appear to divide into a high and low polarization class as well.…”
Section: Introductionmentioning
confidence: 64%
“…On the other hand, DHS predicts radial polarization for scattering angles < ∼ 70 • (forward scattering) and 140 • −160 • (backward scattering), noting that different values of f max can remove the negative branch for forward scattering angles (Min et al 2005). Radial polarization at large scattering angles (backward scattering) has been observed at optical and NIR wavelengths in a number of comets (Kelley et al 2004;Woodward et al 2011), and dust grains in protoplanetary disks can have similar compositions to those found in comets (Bouwman et al 2003). Experimental measurements in the optical show that ensembles of arbitrarily shaped dust aggregates also produce radial polarization patterns at large scattering angles (Muñoz et al 2000(Muñoz et al , 2006Volten et al 2007).…”
Section: The Effect Of Dust Propertiesmentioning
confidence: 99%
“…Any nonazimuthal polarization is associated with noise and/or calibration errors. While this is valid when single scattering dominates in nearly face-on disks, the assumption may break down for higher disk inclinations and for peculiar dust properties (as for those of comets, e.g., Kelley et al 2004), when grains are aligned (Matsumura & Seki 1996;Wolf et al 2002), and/or when disks are optically thick and multiple scattering occurs (Bastien & Menard 1988). In this letter, we explore some of these deviations and quantify their impact on the use of the radial-Stokes formalism at near-infrared (NIR) wavelengths.…”
Section: Introductionmentioning
confidence: 99%